Gene variants polymorphisms and uterine leiomyoma: an updated review - Upadhyay, Sonal; Dubey, Pawan K. (Frontiers in Genetics, 2024)
Uterine leiomyoma, commonly referred to as fibroids, is a benign tumor that develops in the muscular wall of the uterus. These growths are non-cancerous and can vary in size, ranging from tiny nodules to larger masses. Uterine leiomyomas often occur during a woman's reproductive years and can lead to symptoms such as heavy menstrual bleeding, pelvic pain, and pressure on nearby organs. While the exact cause is not fully understood, hormonal factors, particularly estrogen and progesterone, are believed to play a role in their development. The exploration of connections between genetic variants and uterine leiomyoma has captivated scientific attention for numerous years. The results from investigations remain a subject of intrigue within the scientific community. To date, the findings regarding the relationships between single nucleotide polymorphisms (SNPs) and uterine leiomyoma have exhibited some inconsistencies. However, amidst these inconsistencies, several promising outcomes have emerged that hold the potential to shape future research endeavors. These promising leads could pave the way for the development of innovative targeted therapies and novel prognostic biomarkers. This review specifically centers on accentuating the existing literature data concerning genetic variants that have been explored for their potential connections to uterine leiomyoma. Additionally, it underscores the prospects of employing genetic variations as diagnostic and prognostic biomarkers for individuals diagnosed with uterine leiomyoma.